TIDE Analysis of Cryptosporidium Infections by gp60 Typing Reveals Obscured Mixed Infections. (21st August 2021) - Dettwiler, Ines; Troell, Karin; Robinson, Guy; Chalmers, Rachel M; Basso, Walter; Rentería-Solís, Zaida Melina; Daugschies, Arwid; Mühlethaler, Konrad; Dale, Mariko I; Basapathi Raghavendra, Jyothi; Ruf, Marie-Thérèse; Poppert, Sven; et al.
Abstract: Background: Cryptosporidiosis is a parasitic disease associated with potentially fatal diarrhea. The most used method in Cryptosporidium subtyping is based on the glycoprotein gene gp60 . Each infection can represent a parasite population, and it is important to investigate the influence on transmission and virulence, as well as any impact on public health investigations. However, an easy-to-use method for detection is lacking. Methods: Here we report on the use of the bioinformatic program TIDE for deconvolution of gp60 chromatograms. A combination of single oocyst analysis and cloning successfully confirmed the within-sample parasite population diversity. Retrospective sample analysis was conducted on archived chromatograms. Results: For Cryptosporidium parvum, 8.6% multistrain infections (13 of 152) obscured by currently used consensus base calling were detected. Importantly, we show that single oocysts can harbor a mixed population of sporozoites. We also identified a striking dominance of unappreciated polymerase stutter artefacts in all 218 chromatograms analyzed, challenging the uncritical use of gp60 typing. Conclusions: We demonstrate the value of a new, easy-to-use analytical procedure for critical characterization of C. parvum and Cryptosporidium hominis in epidemiological investigations, also applicable retrospectively. Our findings illuminate the hidden parasite diversity with important implications for tracing zoonotic and person-to-person transmissions. Abstract : Cryptosporidium infections are frequently caused by a population of parasites. Mixed infections are detectable by TIDE analysis of chromatograms. Polymerase stutter can obscure gp60 subtyping method. Hidden parasite diversity has important implications for public health investigations.